﻿Population structure and density of a new invasive species Rangia cuneata in the Szczecin Lagoon (Odra/Oder estuary, Poland) - Przemysław Czerniejewski; Jarosław Dąbrowski; Adam Brysiewicz; Krzysztof Formicki (Aquatic Invasions)
The native North American bivalve species Rangia cuneata was unintentionally introduced into European waters during the first decade of the 21st century. In the Baltic Sea, it is mostly found along the southeastern coast, but in 2018 researchers also discovered the species in the Bay of Pomerania, which indicated that it could eventually inhabit the adjacent Szczecin Lagoon and Odra River. In 2021, the species was discovered for the first time in the Szczecin Lagoon during a sampling campaign, at 5 out of the 12 dispersed study sites with diverse bottom substrates. The goal of this study was to ascertain R. cuneata population density, morphometric parameters, individual growth, and the potential for further expansion in the southern Baltic Sea waters. For the study, 201 individuals of this species were collected. Compared to other sites in the southeast Baltic, the Szczecin Lagoon had a much lower average R. cuneata population density, at 13.2 ± 7.11 individuals m-2 of the bottom area. The highest population density was found at sites with more silt (4–63 µm) and less sand (>63 µm). R. cuneata shells had an average length of 30.9 ± 4.6 mm and an average weight of 6.6 ± 2.8 g. The collected specimens were greater in size than other populations of the species in the Baltic Sea and were comparable in size to populations from the nearby Bay of Pomerania. There were no specimens that were under 10 mm in length, and the population was dominated by specimens in the 25–30 mm and 30–35 mm ranges, as well as the 3+ and 4+ age groups. Given the R. cuneata’s invasive potential and its fast rate of colonization of new areas, it would be prudent to monitor this population and the species migration patterns across the estuary waters of the western Baltic.